Composite film and preparation method thereof, light-emitting device and display device

By adopting the composite film design in the light emitting device and using the metal oxide laminated structure of the functional layer and the interface modification layer, the problems of metal oxide layer stability and carrier transmission performance are solved, and more efficient hole carrier transmission and more stable light emitting device performance are achieved.

CN119630177APending Publication Date: 2025-03-14GUANGDONG JUHUA PRINTING DISPLAY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311191951.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-14
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the existing OLED and QLED light emitting devices, the stability of the metal oxide layer is poor, and the carrier transmission performance needs to be further improved.

Method used

A composite film is adopted, including a functional layer and an interface modification layer. The functional layer is composed of a first metal oxide, and the interface modification layer is composed of a second metal oxide and a metal chalcogen compound, and the carrier transmission efficiency is improved through the laminated structure.

Benefits of technology

By reducing the potential barrier of the interface modification layer, the hole carrier mobility and hole transport efficiency are improved, and the stability and performance of the light emitting device are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119630177A_ABST
    Figure CN119630177A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to the field of display, in particular to a composite film and a preparation method thereof, a light-emitting device and a display device, and the composite film comprises a functional layer and an interface modification layer which are sequentially stacked; the material of the functional layer comprises a first metal oxide; and the material of the interface modification layer comprises a second metal oxide and a metal chalcogenide. According to the invention, the carrier mobility is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of display technology, and in particular to a composite film and a preparation method thereof, a light-emitting device and a display apparatus. Background Art

[0002] Currently, the widely used light-emitting devices are organic light-emitting diodes (OLEDs) and quantum dot light-emitting diodes (QLEDs). OLED has become the mainstream technology in the field of display technology due to its excellent display performance, such as self-luminescence, simple structure, ultra-thinness, fast response speed, wide viewing angle, low power consumption, and flexible display. QLED has the advantages of saturated color of emitted light, adjustable wavelength, low start-up voltage, good solution processability, easy fine control of quantum dots, and high quantum yield of photoluminescence and electroluminescence. In recent years, it has become a strong competitor of OLED.

[0003] OLED and QLED devices can be provided with a metal oxide layer to improve carrier transport performance; however, the stability of the metal oxide layer is poor and the carrier transport performance needs to be further improved. Summary of the invention

[0004] Based on this, the embodiments of the present application provide a composite film and a method for preparing the same, a light-emitting device, and a display device.

[0005] In order to solve the above technical problems, the present application provides a composite film, which adopts the following technical solution:

[0006] A composite film comprising a functional layer and an interface modification layer stacked in sequence;

[0007] The material of the functional layer includes a first metal oxide; the material of the interface modification layer includes a second metal oxide and a metal chalcogenide.

[0008] In order to solve the above technical problems, the present application provides a method for preparing a composite film, which adopts the following technical solution:

[0009] A method for preparing a composite film, comprising:

[0010] providing a substrate;

[0011] Disposing a functional material solution on the substrate to form a functional layer, wherein the functional material solution includes a first metal oxide;

[0012] An interface modification solution is arranged on the functional layer to form an interface modification layer to obtain a composite film, wherein the interface modification solution includes a second metal oxide and a metal sulfide compound.

[0013] In order to solve the above technical problems, the embodiment of the present application provides a light emitting device, which adopts the following technical solution:

[0014] A light-emitting device comprises a first electrode, a hole functional layer, a light-emitting layer and a second electrode stacked in sequence;

[0015] Wherein, the hole functional layer comprises a composite film, and the composite film is the composite film as described above, or is made by the composite film preparation method as described above.

[0016] In order to solve the above technical problems, the present application provides a display device, which adopts the following technical solution:

[0017] A display device, comprising a light emitting device;

[0018] Wherein, the light-emitting device is the light-emitting device described above.

[0019] Compared with the prior art, the embodiments of the present application have the following beneficial effects: in the composite film of the present application, both the interface modification layer and the functional layer contain metal oxides, which makes it easy for the two to connect and recombine and is beneficial to the transmission of carriers, and utilizes the characteristic that the electronegativity of the sulfide element in the interface modification layer is less than that of the oxygen element, thereby reducing the potential barrier of the interface modification layer and further improving the hole carrier mobility and hole transmission efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the scheme of the present application, a brief introduction is given below to the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0021] Figure 1 is a schematic diagram of the structure of the composite film of an embodiment of the present application;

[0022] Figure 2 is a flow chart of the preparation of the composite film of the embodiment of the present application;

[0023] Figure 3 It is a schematic diagram of the structure of the light-emitting device of an embodiment of the present application.

[0024] Reference numerals:

[0025] 11. Functional layer; 12. Interface modification layer; 30. Light-emitting device; 31. First electrode; 32. Hole injection layer; 33. Hole functional layer; 34. Light-emitting layer; 35. Electron transport layer; 36. Electron injection layer; 37. Second electrode. DETAILED DESCRIPTION

[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by technicians in the technical field of this application; the terms used in the specification of the application herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned drawings are intended to cover non-exclusive inclusions. The terms "first", "second", etc. in the specification and claims of this application or the above-mentioned drawings are used to distinguish different objects, not to describe a specific order.

[0027] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0028] See also Figure 1 An embodiment of the present application provides a composite film, comprising a functional layer 11 and an interface modification layer 12 stacked in sequence; the material of the functional layer 11 comprises a first metal oxide; the material of the interface modification layer 12 comprises a second metal oxide and a metal sulfide compound.

[0029] In the composite film of the present application, both the interface modification layer 12 and the functional layer 11 contain metal oxides, which make it easy for the two to connect and recombine and facilitate carrier transport. In addition, the electronegativity of the sulfide element in the interface modification layer 12 is less than that of the oxygen element, so as to reduce the potential barrier of the interface modification layer 12, making it easier for the functional layer 11 to transport hole carriers, thereby further improving the hole carrier mobility and the hole transport efficiency.

[0030] In some embodiments, the first metal oxide and the second metal oxide are independently selected from at least one of cuprous oxide, ferric oxide, manganese oxide, tungsten dioxide, and nickel oxide.

[0031] In some embodiments, the weight percentage of oxygen in the second metal oxide is 10 to 50 wt %. Within this range, as the weight percentage of oxygen in the second metal oxide gradually increases, the number of oxygen vacancies in the second metal oxide increases, which can be used to capture more electron carriers to prevent the electron carriers from being transmitted to the functional layer 11 through the interface modification layer 12, thereby improving the stability of the functional layer 11; and within this range, the second metal oxide has more metal elements, so that the second metal oxide has good electrical conductivity, further improving the hole carrier transmission efficiency of the functional layer 11.

[0032] Optionally, the weight percentage of oxygen element in the first metal oxide is selected from the range formed by any one of 10wt%, 12wt%, 14wt%, 16wt%, 18wt%, 20wt%, 22wt%, 24wt%, 26wt%, 28wt%, 30wt%, 32wt%, 34wt%, 36wt%, 38wt%, 40wt%, 42wt%, 44wt%, 46wt%, 48wt%, and 50wt%, or any two of them.

[0033] In some embodiments, the metal chalcogenide compound includes at least one of a metal sulfide, a metal selenide, and a metal telluride.

[0034] Optionally, the metal sulfide is selected from at least one of cuprous sulfide, iron sulfide, manganese sulfide, tungsten disulfide and nickel sulfide.

[0035] Optionally, the metal selenide includes at least one of cuprous selenide, iron selenide, manganese selenide, tungsten selenide, and nickel selenide.

[0036] Optionally, the metal telluride includes at least one of cuprous telluride, iron telluride, manganese telluride, tungsten ditelluride, and nickel telluride.

[0037] In some embodiments, at least two of the first metal oxide, the metal chalcogenide, and the second metal oxide have the same metal element. The same metal element can reduce interface defects between different compounds, thereby reducing the interface transmission barrier of hole carriers between different compounds, thereby improving the transmission efficiency of hole carriers.

[0038] It can be understood that when the metal elements of the first metal oxide and the second metal oxide and / or the metal sulfide compound are the same, the interface transmission barrier of hole carriers between the functional layer 11 and the interface modification layer 12 can be reduced, thereby improving the transmission efficiency of hole carriers; when the metal elements of the second metal oxide and the metal sulfide compound are the same, the interface transmission barrier of hole carriers between the second metal oxide and the metal sulfide compound in the interface modification layer 12 can be reduced, thereby improving the transmission efficiency of hole carriers.

[0039] In some embodiments, the thickness ratio of the functional layer 11 to the interface modification layer 12 is (30-50):(5-10).

[0040] Optionally, the thickness ratio of the functional layer 11 to the interface modification layer 12 is selected from the range formed by any one or any two of 30:5, 30:7, 30:9, 30:10, 35:5, 35:7, 35:9, 35:10, 40:5, 40:7, 40:9, 40:10, 45:5, 45:7, 45:9, 45:10, 50:5, 50:7, 50:9, 50:10.

[0041] In some embodiments, the functional layer 11 further comprises a carbon material, and the first metal oxide is supported on the carbon material. The carbon material is used to improve the transmission efficiency of hole carriers in the functional layer 11.

[0042] Optionally, the carbon material includes at least one of graphene oxide, carbon fiber, carbon nanotube, carbon 60, graphite, and activated carbon.

[0043] Preferably, the carbon material is graphene oxide. When graphene oxide is in an oxidized state, the sp2 hybrid conjugation of graphene itself is destroyed, resulting in a lack of freely moving electron carriers, and it is in an insulating state, while having a wide energy band gap; when graphene oxide is in a reduced state, freely moving electron carriers can be generated in the conjugated region, making it in a conductive state; thus, using graphene oxide as the functional layer 11 can improve the transmission efficiency of hole carriers, thereby improving the luminescence effect of the light-emitting device.

[0044] In some embodiments, the mass ratio of the carbon material to the first metal oxide is 1:(0.5-1.2).

[0045] Optionally, the mass ratio of the carbon material to the first metal oxide is selected from any one of 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.17, 1:1.2, or a range formed by any two of them.

[0046] In some embodiments, the weight percentage of carbon element and metal element in the functional layer 11 is (3-8):1.

[0047] Optionally, the weight percentage of the carbon element and the metal element in the functional layer 11 is selected from any one of 3:1, 4:1, 5:1, 6:1, 7:1, 8:1 or a range formed by any two of them.

[0048] In some embodiments, the surface of the carbon material is modified with a basic functional group, so that the functional layer 11 has a basic property. In this way, when the functional layer 11 of the present application is disposed on an acidic film layer, the basic molecules in the functional layer 11 can be used to neutralize the acidic molecules on the acidic film layer to prevent the acidic molecules from corroding the material of the functional layer 11, thereby extending the service life of the functional layer 11.

[0049] In some embodiments, the basic functional group includes a hydroxyl functional group and / or an amino functional group. Both the hydroxyl functional group and the amino functional group are basic functional groups, and the hydroxyl functional group is more basic than the amino functional group, so that the formed functional layer 11 can more effectively inhibit acidic molecules.

[0050] In some embodiments, the material of the interface modification layer 12 includes a core and a shell layer covering the core, the core includes the second metal oxide, and the shell layer includes the metal chalcogenide.

[0051] In this embodiment, in the core-shell structure, electrons are confined in the shell layer, while holes exist in the inner core body. Due to the layered arrangement of the core-shell structure, electrons and holes are separated in space, reducing the interaction between them, thereby inhibiting electron-hole recombination, thereby improving the stability of the composite film and extending the service life of the composite film; at the same time, the interface between the core body and the shell layer has strong adaptability, reducing the stress and strain when the two are in contact, thereby improving the stability of the interface modification layer 12.

[0052] In some embodiments, the particle size of the material of the interface modification layer is 2 to 8 nm.

[0053] Optionally, the particle size of the material of the interface modification layer is selected from the range formed by any one or two of 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, and 8 nm.

[0054] In some embodiments, the ratio of the thickness of the shell layer to the diameter of the core body is 1:(2-8).

[0055] Optionally, the ratio of the thickness of the shell layer to the diameter of the core body is selected from the range formed by any one of 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8 or any two of them.

[0056] In some embodiments, the mass ratio of the second metal oxide to the metal chalcogenide compound in the interface modification layer 12 is 1:(0.2-0.5).

[0057] Optionally, the mass ratio of the second metal oxide to the metal chalcogenide compound in the interface modification layer 12 is selected from any one of 1:0.5, 1:0.4, 1:0.3, 1:0.2 or a range formed by any two of them.

[0058] See also Figure 2 The present application also provides a method for preparing a composite film, which is used to prepare the composite film as described above. The method for preparing the composite film includes:

[0059] Step S21, providing a substrate.

[0060] In this embodiment, when the substrate is used for preparing a light-emitting device, it can be a light-emitting device preform, and the preform includes a first electrode, or the preform includes a first electrode and a hole injection layer that are stacked.

[0061] Step S22, placing a functional material solution on the substrate to form a functional layer, wherein the functional material solution includes a first metal oxide;

[0062] Step S23, placing an interface modification solution on the functional layer to form an interface modification layer to obtain a composite film, wherein the interface modification solution includes a second metal oxide and a metal chalcogenide compound.

[0063] In the prepared composite film, both the interface modification layer and the functional layer include metal oxides, which make the two easy to connect and recombine, and are beneficial to the transmission of carriers. The characteristic that the electronegativity of the sulfide element in the interface modification layer is smaller than that of the oxygen element is further utilized to reduce the potential barrier of the interface modification layer, making it easier for the functional layer to transmit hole carriers, further improving the hole carrier mobility and hole transmission efficiency.

[0064] In some embodiments, a solution method can be used to set a functional material solution on a substrate / set an interface modification solution on a functional layer; wherein the solution method includes but is not limited to a sol-gel method, printing, inkjet printing, spin coating, coating, etc.

[0065] In some embodiments, in the step S22, before providing the functional material solution on the substrate, the step further includes:

[0066] Step S221, providing a first metal oxide precursor solution and a carbon material solution.

[0067] In some embodiments, the volume ratio of the first metal oxide precursor solution to the carbon material solution is (0.01-0.5):1.

[0068] Optionally, the volume ratio of the first metal oxide precursor solution to the carbon material solution is selected from the range formed by any one of 0.01:1, 0.05:1, 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1, 0.35:1, 0.4:1, 0.45:1, and 0.5:1, or any two of them.

[0069] In some embodiments, the first metal oxide precursor includes a first metal oxide precursor and a first solvent.

[0070] In some embodiments, the first metal oxide precursor includes at least one of copper acetate, ferric phosphate, manganous oxalate, ammonium tungstate, and nickel nitrate.

[0071] In some embodiments, the first solvent includes an aromatic hydrocarbon solvent, and the aromatic hydrocarbon solvent includes at least one of benzene, toluene, and xylene.

[0072] In some embodiments, the concentration of the first metal oxide precursor in the first metal oxide precursor solution is 0.01-0.05 g / mL.

[0073] Optionally, the concentration of the first metal oxide precursor in the first metal oxide precursor solution is selected from the range formed by any one of 0.01 g / mL, 0.02 g / mL, 0.03 g / mL, 0.04 g / mL, 0.05 g / mL or any two of them.

[0074] In some embodiments, the carbon material solution includes a carbon material and a second solvent.

[0075] In some embodiments, the carbon material includes at least one of graphene oxide, carbon fiber, carbon nanotube, carbon 60, graphite, and activated carbon.

[0076] In some embodiments, the second solvent includes an alcohol solvent, N,N-dimethylformamide, and deionized water, and the alcohol solvent includes at least one of methanol, ethanol, and isopropanol.

[0077] In some embodiments, the concentration of the carbon material in the carbon material solution is 0.02-0.05 g / mL.

[0078] Optionally, the concentration of the carbon material in the carbon material solution is selected from the range formed by any one of 0.02 g / mL, 0.03 g / mL, 0.04 g / mL, 0.05 g / mL, or any two of them.

[0079] In some embodiments, before the step S221 of providing the first metal oxide precursor solution and the carbon material solution, the step further includes:

[0080] Step S2211, dissolving the carbon material in the acidic solution to obtain a target solution.

[0081] In this step, the carbon material is added to the acidic solution to utilize the acidic solution to oxidize the carbon material to form carbon oxides, the surface of which has more functional groups that can interact with other molecules in the solution, thereby enhancing the dispersibility of the carbon oxides in the solution.

[0082] Step S2212: under alkaline conditions, mixing the target solution and the alkaline solution to obtain an alkaline carbon material solution.

[0083] In this step, the alkaline condition is used to control the pH value of the first solution containing the alkaline carbon material obtained by mixing, thereby controlling the content of the alkaline functional groups in the first solution.

[0084] For example, the alkaline solution is a sodium hydroxide solution. In practical applications, 130ul of 0.2mol / Ld of sodium hydroxide solution is added to 10mL of the first target solution, so that the sodium hydroxide reacts with the acidic substance in the first target solution to neutralize the acid and base, and the pH value of the formed first solution is adjusted by controlling the alkaline conditions, thereby obtaining the first solution containing the alkaline carbon material.

[0085] In some embodiments, the pH value of the alkaline condition is 8 to 10.

[0086] Optionally, the pH value of the alkaline condition is selected from the range formed by any one of 8, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9, 9, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9, 10, or any two of them.

[0087] Step S222: mixing the first metal oxide precursor solution and the carbon material solution to obtain a first mixed solution.

[0088] In some embodiments, ultrasonic treatment may be performed during the mixing of the first metal oxide precursor solution and the carbon material solution so that the first metal oxide precursor solution and the carbon material solution can be fully mixed.

[0089] Step S223, drying the first mixed solution to obtain a functional material.

[0090] In some embodiments, the drying process includes spray drying and annealing. The first mixed solution is first spray dried and then annealed in an inert atmosphere to prevent oxidation of the solid matter. Annealing can reduce residual organic matter and improve the crystallinity of the functional material.

[0091] Step S224, mixing the functional material and the first organic solvent to obtain a functional material solution.

[0092] In some embodiments, the first organic solvent includes at least one of aromatic hydrocarbon solvents, aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, halogenated hydrocarbon solvents, alcohol solvents, ether solvents, ester solvents, ketone solvents, glycol derivative solvents, acetonitrile, and pyridine.

[0093] Optionally, the aromatic hydrocarbon solvent includes at least one of benzene, toluene and xylene.

[0094] Optionally, the aliphatic hydrocarbon solvent includes at least one of pentane, hexane and octane.

[0095] Optionally, the alicyclic hydrocarbon solvent includes at least one of cyclohexane, cyclohexanone and toluene-cyclohexanone.

[0096] Optionally, the halogenated hydrocarbon solvent includes at least one of chlorobenzene, dichlorobenzene and dichloromethane.

[0097] Optionally, the alcohol solvent includes at least one of methanol, ethanol and isopropanol.

[0098] Optionally, the ether solvent includes at least one of diethyl ether and propylene oxide.

[0099] Optionally, the ester solvent includes at least one of methyl acetate, ethyl acetate and propyl acetate.

[0100] Optionally, the ketone solvent includes at least one of acetone, methyl butyl ketone and methyl isobutyl ketone.

[0101] Optionally, the diol derivative solvent includes at least one of ethylene glycol monomethyl ether, ethylene glycol monoethyl ether and ethylene glycol monobutyl ether.

[0102] In some embodiments, in step S23, before the step of providing an interface modification solution on the functional layer, the step further includes:

[0103] Step S231 , providing a second metal oxide precursor solution and a metal chalcogenide precursor solution.

[0104] In some embodiments, the volume ratio of the second metal oxide precursor solution to the metal chalcogenide compound precursor solution is 1:(5-10).

[0105] Optionally, a volume ratio of the second metal oxide precursor solution to the metal chalcogenide compound precursor solution is selected from any one of 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or a range formed by any two of them.

[0106] In some embodiments, the second metal oxide precursor solution includes a second metal precursor and a third solvent.

[0107] In some embodiments, the concentration of the second metal precursor in the second metal oxide precursor solution is 0.2-0.8 mol / L.

[0108] Optionally, the concentration of the second metal precursor in the metal oxide precursor solution is selected from the range formed by any one of 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, and 0.8 mol / L, or any two of them.

[0109] In some embodiments, the second metal oxide precursor includes at least one of copper acetate, ferric phosphate, manganous oxalate, ammonium tungstate, and nickel nitrate.

[0110] In some embodiments, the first solvent includes an aromatic hydrocarbon solvent, and the aromatic hydrocarbon solvent includes at least one of benzene, toluene, and xylene.

[0111] In some embodiments, the metal chalcogenide precursor solution includes a metal chalcogenide precursor and a fourth solvent.

[0112] In some embodiments, the metal chalcogenide compound precursor is at least one of a metal sulfide precursor, a metal selenide precursor, and a metal telluride precursor.

[0113] Optionally, the metal sulfide precursor is selected from at least one of sodium sulfide, potassium sulfide, calcium sulfide, magnesium sulfide, aluminum sulfide, and zinc sulfide.

[0114] Optionally, the metal selenide precursor is selected from at least one of sodium selenide, potassium selenide, calcium selenide, magnesium selenide, aluminum selenide, and zinc selenide.

[0115] Optionally, the metal telluride precursor is selected from at least one of sodium telluride, potassium telluride, calcium telluride, magnesium telluride, aluminum telluride, and zinc telluride.

[0116] In some embodiments, the fourth solvent includes at least one of an aromatic hydrocarbon solvent, an alcohol solvent, an ether solvent, an ester solvent, and a ketone solvent.

[0117] Optionally, the aromatic hydrocarbon solvent includes at least one of benzene, toluene and xylene; the alcohol solvent includes at least one of methanol, ethanol and isopropanol.

[0118] Optionally, the ether solvent includes at least one of diethyl ether and propylene oxide; the ester solvent includes at least one of methyl acetate, ethyl acetate and propyl acetate.

[0119] Optionally, the ketone solvent includes at least one of acetone, methyl butyl ketone and methyl isobutyl ketone.

[0120] Step S232 , mixing the second metal compound precursor solution and the metal chalcogenide compound precursor to obtain a second mixed solution.

[0121] Step S233, mixing the second mixed solution and the second organic solvent to obtain an interface modification solution.

[0122] In some embodiments, the second organic solvent includes at least one of aromatic hydrocarbon solvents, aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, halogenated hydrocarbon solvents, alcohol solvents, ether solvents, ester solvents, ketone solvents, glycol derivative solvents, acetonitrile, and pyridine.

[0123] Optionally, the aromatic hydrocarbon solvent includes at least one of benzene, toluene and xylene.

[0124] Optionally, the aliphatic hydrocarbon solvent includes at least one of pentane, hexane and octane.

[0125] Optionally, the alicyclic hydrocarbon solvent includes at least one of cyclohexane, cyclohexanone and toluene-cyclohexanone.

[0126] Optionally, the halogenated hydrocarbon solvent includes at least one of chlorobenzene, dichlorobenzene and dichloromethane.

[0127] Optionally, the alcohol solvent includes at least one of methanol, ethanol and isopropanol.

[0128] Optionally, the ether solvent includes at least one of diethyl ether and propylene oxide.

[0129] Optionally, the ester solvent includes at least one of methyl acetate, ethyl acetate and propyl acetate.

[0130] Optionally, the ketone solvent includes at least one of acetone, methyl butyl ketone and methyl isobutyl ketone.

[0131] Optionally, the diol derivative solvent includes at least one of ethylene glycol monomethyl ether, ethylene glycol monoethyl ether and ethylene glycol monobutyl ether.

[0132] In some embodiments, before the step S23, the step of obtaining the composite film, the step further includes:

[0133] Step S234: etching the interface modification layer using plasma gas.

[0134] In some embodiments, the interface modification layer is etched using plasma gas to bombard the first metal oxide to remove some oxygen atoms on the first metal oxide, thereby generating more oxygen vacancy defects on the first metal oxide and further improving the electron capture capability of the first metal oxide.

[0135] In some embodiments, the plasma gas includes at least one of argon, hydrogen, and nitrogen.

[0136] In some embodiments, the etching process lasts for 10 to 60 minutes.

[0137] Optionally, the etching treatment time is selected from the range formed by any one of 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, and 60 min, or any two of them.

[0138] In some embodiments, the etching process has a power of 110 to 160W.

[0139] Optionally, the power of the etching process is selected from a range formed by any one or any two of 110W, 120W, 130W, 140W, 150W, and 160W.

[0140] In some embodiments, the RF frequency of the etching process is 10 to 15 MHz.

[0141] Optionally, the radio frequency frequency of the etching process is selected from a range formed by any one or any two of 10W, 11W, 12W, 13W, 14W, and 15W.

[0142] In some embodiments, the pressure of the etching process is 80 to 120 Pa.

[0143] Optionally, the radio frequency frequency of the etching process is selected from a range formed by any one or two of 80Pa, 90Pa, 100Pa, 110Pa, and 120Pa.

[0144] In some embodiments, under the above-mentioned etching process conditions such as power, radio frequency, and pressure, the plasma gas can generate more oxygen vacancies in the first metal oxide while having little effect on the morphology of the interface modification layer.

[0145] See also Figure 3 The embodiment of the present application further provides a light emitting device 30, comprising a first electrode 31, a hole functional layer 33, a light emitting layer 34 and a second electrode 37 stacked in sequence;

[0146] The hole functional layer 33 includes a composite film, and the composite film is the composite film as described above, or is made by the composite film preparation method as described above.

[0147] In this embodiment, in the composite film of the hole functional layer 33, the interface modification layer 12 and the functional layer 11 both contain metal oxides, which makes the two easy to connect and recombine and is beneficial to the transmission of carriers. In addition, the electronegativity of the sulfide element in the interface modification layer 12 is less than that of the oxygen element, so as to reduce the potential barrier of the interface modification layer 12, thereby further improving the hole carrier mobility and the hole transmission efficiency.

[0148] In some embodiments, the functional layer is disposed close to the first electrode, and the interface modification layer is disposed close to the light-emitting layer. In this way, the interface modification layer can inhibit the transmission of electron carriers in the light-emitting layer to the functional layer, thereby improving the stability of the functional layer and extending the service life of the light-emitting device.

[0149] In some embodiments, the materials of the first electrode 31 and the second electrode 37 independently include at least one of a metal material, a carbon material and a metal oxide, the metal material includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes a doped or undoped metal oxide, the doped metal oxide includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, or includes a composite electrode in which a metal is sandwiched between doped or undoped transparent metal oxides, the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2.

[0150] In some embodiments, the light-emitting layer 34 is a quantum dot light-emitting layer 34 or an organic light-emitting layer 34; the material of the quantum dot light-emitting layer 34 includes at least one of a single structure quantum dot and a core-shell structure quantum dot, and the material of the single structure quantum dot, the core material of the core-shell structure quantum dot and the shell material of the core-shell structure quantum dot are independently selected from at least one of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds, wherein the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS , at least one of HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, the IV-VI group compound At least one selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe, and the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, At least one of AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs or InAlPSb, and the I-III-VI group compound is at least one of CuInS2, CuInSe2 and AgInS2;The material of the organic light-emitting layer 34 includes at least one of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine-C2,N)iridium(III), 4,4',4"-tris(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine-C2,N)iridium, diarylanthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials and DBP fluorescent materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives.

[0151] In some embodiments, the light-emitting device 30 further includes a hole injection layer 32 disposed between the first electrode 31 and the hole functional layer 33; the material of the hole injection layer 32 includes at least one of TFB, CuPc, PVK, Poly-TPD, PFB, DNTPD, TCATA, TCCA, CBP, TPD, NPB, NPD, PEDOT:PSS, TAPC, MCC, F4-TCNQ, HATCN, 4,4',4'-tri(N-3-methylphenyl-Nphenylamino)triphenylamine, polyaniline, transition metal oxides, transition metal sulfides, transition metal tinides, doped graphene, undoped graphene, C60, polyester copper carbonate, and molybdenum trioxide.

[0152] In some embodiments, the light-emitting device 30 further includes an electron transport layer 35 and / or an electron injection layer 36 disposed between the light-emitting layer 34 and the second electrode 37; the materials of the electron transport layer 35 and the electron injection layer 36 independently include inorganic materials and / or organic materials; the inorganic materials include doped or undoped zinc oxide, barium oxide, aluminum oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, zinc oxide One or more of lithium, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate; the doped elements include at least one of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic material includes at least one of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds, hydroxyquinoline compounds, polythiophene compounds, perylene imide compounds, and fullerene compounds. Wherein: the fluorene-containing compounds include one or more of WPF-oxy-F, WPF-6-oxy-F, PF-EP, PFNBr, PFSO3Na, PFBTBr, 3TPA-FEP, PF-NS, PF-N-SOC8, FFiF, FPF, ZnO:PFN, PmP-NOH, PmP36F-NOH, PFBD, PEI:PF1, FCF, PF15-b-PDMAEMA75; the polythiophene compounds include P3HTN, PT3SB, P One or more of T2BTDPPSB, PT2NDISB, PT6N, PBTAZPOBr, PCPDTTPD-Im; the perylene imide compounds include one or more of PDINO, PDIP, PBI-H, FPDI, PDIN, PTCDI-C8; the fullerene compounds include one or more of DMAPA-C60, C60-ETA, C60-PEG, rGO-pyrene-PCBM, FPI-PEIE, Fullerenol.

[0153] The present application also provides a display device, comprising the light-emitting device as described above.

[0154] In this embodiment, the display device includes a plurality of light-emitting devices, each of which has a hole functional layer containing a composite film. In the interface modification layer of the hole composite film, the interface modification layer and the functional layer both contain metal oxides, so that the two are easy to connect and recombine and are conducive to the transmission of carriers. In addition, by utilizing the characteristic that the electronegativity of the sulfide element in the interface modification layer is less than that of the oxygen element, the potential barrier of the interface modification layer is reduced, making it easier for the functional layer to transmit hole carriers, thereby further improving the hole carrier mobility and the hole transmission efficiency.

[0155] The technical scheme and technical effects of the present application are described in detail below through specific examples and comparative examples. The following examples are only some examples of the present application and do not specifically limit the present application.

[0156] Composite film embodiment 1:

[0157] Step 1: providing a substrate.

[0158] Step 2: Mix 50 mL of concentrated sulfuric acid and 30 mL of concentrated nitric acid in a 5°C water bath, add 3 g of graphite and stir for 30 min to fully dissolve, then add 33 g of potassium chlorate powder, then stop the ice water bath, react at room temperature for 96 h, and then pour the mixed solution into 20 mL of deionized water to obtain a graphene oxide dispersion with a concentration of 0.03 mg / mL and a volume of 100 mL. Add 11 mL of 0.02 g / mL cupric acetate solution was ultrasonically dispersed for 30 minutes, and then the mixed solution was spray dried (inlet temperature 200°C, outlet temperature 110°C) to obtain a brown powder, and the brown powder was annealed at 210°C for 60 minutes under argon protection to decompose cupric acetate, and naturally cooled to obtain a cuprous oxide-loaded graphene oxide nanosheet black powder with a mass ratio of cuprous oxide to graphene oxide nanosheets of 1:0.8 and a carbon-copper atomic ratio of 5:1, and the cuprous oxide-loaded graphene oxide nanosheet black powder was dissolved in an ethanol solvent to obtain a functional material solution, and 12 drops of the functional material solution were inkjet printed on a substrate to form a functional layer with a thickness of 30 nm; wherein the volume ratio of the cupric acetate solution to the graphene oxide dispersion was 0.11:1.

[0159] Step 3: 0.7 mol / L trisodium citrate and 1.2 mol / L sodium carbonate were mixed evenly, and then mixed with 0.68 mol / L copper sulfate, and then 0.5 mol / L of reducing agent glucose was added to the mixture, and the mixture was reacted in a water bath at 80°C for 10 minutes, and centrifuged to obtain cuprous oxide nanoparticles, and then 0.6 g of cuprous oxide nanoparticles were weighed and dispersed in 20 mL of deionized water, and ultrasonically dispersed for 20 minutes to obtain a cuprous oxide dispersion with a concentration of 0.2 mol / L. 150 mL of a 3 mol / L sodium sulfide solution was added, reacted for 5 minutes, centrifuged and washed to obtain a cuprous oxide / cuprous sulfide core-shell structure solution, which was then dissolved in an ethanol solvent to obtain an interface modification solution, and 6 drops of the interface modification solution were inkjet printed on the functional layer to form an interface modification layer of a cuprous oxide / cuprous sulfide core-shell structure with a thickness of 10 nm to obtain a composite film; wherein the weight percentage of oxygen in the cuprous oxide was 11.1 wt%, and the volume ratio of the cuprous oxide dispersion to the sodium sulfide solution was 1:7.5.

[0160] Composite film embodiment 2:

[0161] The difference between Composite Film Example 2 and Composite Film Example 1 is that: in step 2 of this embodiment, the mass of graphite is changed to 2.8 g, and the volume and mass of the cupric acetate solution are changed to 50 mL and 0.025 g / mL respectively; accordingly, the concentration of the obtained graphene oxide dispersion is 0.028 mg / mL, and natural cooling is performed to obtain a black powder of graphene oxide nanosheets loaded with cuprous oxide, with a mass ratio of cuprous oxide to graphene oxide nanosheets of 1:0.5 and a carbon-copper atomic ratio of 3:1.

[0162] Composite film embodiment 3:

[0163] The difference between composite film embodiment 3 and composite film embodiment 1 is that: in step 2 of this embodiment, the mass of graphite is changed to 4.3 g, and the volume and mass of the cupric acetate solution are changed to 10 mL and 0.02 g / mL, respectively; accordingly, the concentration of the obtained graphene oxide dispersion is 0.043 mg / mL, and natural cooling is performed to obtain a cuprous oxide-to-graphene oxide nanosheet mass ratio of 1:1.17 and a carbon-copper atomic ratio of 7:1 to obtain a black powder of graphene oxide nanosheets loaded with cuprous oxide.

[0164] Composite film embodiment 4:

[0165] The difference between composite film embodiment 4 and composite film embodiment 1 is that: in step three of this embodiment, the prepared interface modification layer is an iron oxide / iron trisulfide core-shell structure; accordingly, 0.13 mol / L of ferric chloride and 0.4 mol / L of sodium hydroxide are evenly mixed, reacted in a 180°C water bath for 10 minutes, and centrifuged to obtain compressed nanoparticles, then 0.6 g of iron oxide is weighed and dispersed in 20 mL of deionized water, ultrasonically dispersed for 20 minutes, and an iron oxide dispersion with a concentration of 0.2 mol / L is obtained. 150 mL of 3 mol / L sodium sulfide solution is added to the iron oxide dispersion, reacted for 5 minutes, and centrifuged and washed to obtain an iron oxide / iron trisulfide core-shell structure solution, which is then dissolved in an ethanol solvent, and 6 drops are inkjet printed on the functional layer to form an interface modification layer with a thickness of 10 nm to obtain a composite film, wherein the weight percentage of oxygen element in the iron oxide is 35 wt%, and the volume ratio of the iron oxide dispersion to the sodium sulfide solution is 1:7.5.

[0166] Composite film embodiment 5:

[0167] The difference between composite film embodiment 5 and composite film embodiment 1 is that: in step 2 of this embodiment, the graphene oxide nanosheet dispersion is alkaline, so that the alkaline graphene oxide nanosheet dispersion is used to prepare alkaline graphene oxide nanosheet black powder in step 3; accordingly, after obtaining the graphene oxide dispersion, the graphene oxide dispersion is diluted to 1 mg / mL, and then 130ul0.2mol / Ld sodium hydroxide solution is added to 10mL of the graphene oxide dispersion, and the pH value is controlled at 8 to obtain an alkaline graphene oxide nanosheet dispersion.

[0168] Composite film embodiment 6:

[0169] The difference between Composite Film Example 6 and Composite Film Example 5 is that in step 2 of this example, the pH value is changed to 9.

[0170] Composite film embodiment 7:

[0171] The difference between composite film embodiment 7 and composite film embodiment 5 is that in this embodiment, in step 2, the pH value is changed to 10.

[0172] Composite film examples 8 and 9:

[0173] Composite film embodiment 8 is basically the same as composite film embodiment 1, and composite film embodiment 9 is basically the same as composite film embodiment 5. The differences between composite film embodiment 8 and composite film embodiment 1, and composite film embodiment 9 and composite film embodiment 5 are that: after step three, it also includes: placing the prepared cuprous oxide / cuprous sulfide core-shell structure interface modification layer in an argon and hydrogen mixed gas chamber, with a power of 110 W, a radio frequency of 11 MHz, and a pressure of 80 Pa, and treating for 30 minutes, hydrogen molecules decompose into reactive hydrogen plasma, and the ions bombard the oxygen ions containing weak chemical bonds on the surface of the interface modification layer to form oxygen vacancy defects on the interface modification layer.

[0174] Composite film embodiment 10:

[0175] The difference between composite film embodiment 10 and composite film embodiment 8 is that the power is changed to 150W, the radio frequency frequency is changed to 13.5MHz, and the pressure is changed to 99Pa.

[0176] Composite film embodiment 11:

[0177] The difference between composite film embodiment 11 and composite film embodiment 8 is that the power is changed to 160W, the radio frequency is changed to 15MHz, and the pressure is changed to 115Pa.

[0178] Composite film comparative example 1:

[0179] The difference between the composite film comparative example 1 and the composite film embodiment 1 is that: in the step 2 of this comparative example, cuprous oxide material is arranged on the substrate through an inkjet printing process to obtain a hole functional layer with a thickness of 40 nm; accordingly, step 3 is omitted.

[0180] Experimental test analysis: Single-hole devices were prepared using the composite films obtained from composite film embodiments 1 to 11 and composite film comparison example 1, respectively. The IV relationships of the single-hole devices prepared from composite film embodiments 1 to 11 and comparison example 1 were tested using IVL testing equipment, and the current size of the single-hole device at 2.7V was obtained based on the IV curve. The test results are shown in Table 1.

[0181] Table 1

[0182] Single hole device Current@2.7V(mA) Composite film embodiment 1 69.7 Composite film embodiment 2 75.2 Composite film embodiment 3 56.5 Composite film embodiment 4 50.2 Composite film embodiment 5 84.3 Composite film embodiment 6 85.1 Composite film embodiment 7 85.4 Composite film embodiment 8 82.5 Composite film embodiment 9 89.9 Composite film embodiment 10 85.5 Composite film embodiment 11 87.2 Composite film comparative example 1 10.9

[0183] Referring to Table 1, it can be seen that since the interface modification layer and the functional layer both have metal oxides, the two are easy to transport carriers, and the characteristic that the electronegativity of the sulfide element in the interface modification layer is less than that of the oxygen element is utilized to reduce the potential barrier of the interface modification layer, making it easier for the functional layer to transport hole carriers, further improving the hole carrier mobility and the hole transport efficiency, so that at a driving voltage of 2.7V, the current of the single hole device prepared by the composite film embodiments 1 to 11 of the present application is greater than the current of the single hole device prepared by the composite film comparison example 1.

[0184] Understandably, referring to Table 1, by comparing composite film embodiments 1 to 3, as the mass ratio of cuprous oxide to graphene oxide nanosheets increases, the mass of cuprous oxide increases, so that the functional layer has more cuprous oxide, and because the conductivity of metal is better than that of carbon material, the larger the mass of cuprous oxide, the greater the current of the single-hole device at 2.7V.

[0185] Light emitting device embodiment 1:

[0186] Step 1: providing an ITO substrate as a first electrode.

[0187] Step 2: Poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid) (PEDOT / PSS) is disposed on the first electrode by inkjet printing process to obtain a hole injection layer with a thickness of 40 nm.

[0188] Step three, preparing a composite thin film on the hole injection layer using the method of thin film embodiment 1 to obtain a hole transport layer.

[0189] Step 4: sequentially prepare a red light quantum dot light-emitting layer and an electron transport layer made of zinc oxide on the hole functional layer.

[0190] Step five: evaporate silver on the electron transport layer through an evaporation process to obtain a second electrode with a thickness of 70 nm, thereby obtaining a light-emitting device.

[0191] Light emitting device embodiments 2 to 11:

[0192] The light-emitting device embodiments 2 to 11 are different from the light-emitting device embodiment 1 in that: in step three of the light-emitting device embodiment n, the composite film is prepared by the method of steps two and three in the film embodiment n, where n is 2 to 11.

[0193] Light emitting device comparative example 1:

[0194] The difference between the light-emitting device comparative example 1 and the light-emitting device embodiment 1 is that: in this comparative example, step three is to arrange cuprous oxide material on the hole injection layer through an inkjet printing process to obtain a hole transport layer with a thickness of 40 nm; correspondingly, in step four, a red light quantum dot light-emitting layer and an electron transport layer whose material is zinc oxide are sequentially prepared on the hole transport layer.

[0195] Functional test: The external quantum efficiency (EQE) and lifespan lt95@1000nit of each light-emitting device were tested using the IVL test system. The test results are shown in Table 2.

[0196] Table 2

[0197] LT95@1000nit(h) EQE Light emitting device embodiment 1 10100 10.3% Light emitting device embodiment 2 10500 11% Light emitting device embodiment 3 9800 9.5% Light emitting device embodiment 4 9500 9.8% Light emitting device embodiment 5 12500 13.6% Light emitting device embodiment 6 12800 13.8% Light emitting device embodiment 7 13000 14% Light emitting device embodiment 8 11900 13% Light emitting device embodiment 9 13500 14.3% Light emitting device embodiment 10 12500 13.4% Light emitting device embodiment 11 13000 13.8% Light-emitting device comparative example 1 5000 7.2%

[0198] Referring to Table 2, it can be seen that compared with the hole functional layer of Comparative Example 1, the hole functional layer of Examples 1 to 11 of the present application includes a functional layer and an interface modification layer, wherein both the functional layer and the interface modification layer contain metal oxides, which are beneficial to the connection and recombination of the two, thereby improving the stability of the hole functional layer, and the metal elements in the functional layer and the interface modification layer are the same, thereby reducing the interface resistance and improving the hole transmission efficiency, and the interface modification layer includes cuprous oxide and cuprous sulfide, and the oxygen vacancies of cuprous oxide are used to capture electron carriers to inhibit the transmission of electron carriers to the functional layer, thereby further improving the stability of the hole functional layer, and because the sulfur element contained in the cuprous sulfide shell layer has a lower electronegativity than the oxygen element, thereby reducing the barrier between the interface modification layer and the functional layer, further improving the hole transmission efficiency, and thereby improving the EQE and LT95@1000nit of the light-emitting device,

[0199] Understandably, (1) referring to Table 2, by comparing light-emitting device embodiments 1 to 3, as the mass ratio of cuprous oxide to graphene oxide nanosheets increases, the mass of cuprous oxide increases, so that the functional layer has more cuprous oxide, and since the conductivity of metal is better than that of carbon material, the transmission efficiency of hole carriers in the hole functional layer is improved, and it is also beneficial to the connection and recombination of the functional layer and the interface modification layer, further improving the stability of the hole functional layer, and thus improving the EQE and LT95@1000nit of the device.

[0200] (2) Continuing to refer to Table 2, by comparing light-emitting device embodiments 1 and 4, it can be seen that in light-emitting device embodiment 4, the metal elements in the functional layer and the interface modification layer are different, the metal element in the functional layer is copper, and the metal element in the interface modification layer is iron; however, compared with light-emitting device embodiment 4, the metal elements in the functional layer and the interface modification layer in light-emitting device embodiment 1 are the same, both are copper, so that the functional layer and the interface modification layer are easier to connect and recombine, the interface matching degree between the two is higher, and the interface barrier between the two is also reduced, which is beneficial to the transmission of hole carriers, thereby improving the LT95@1000nit and EQE of the light-emitting device.

[0201] (3) Continuing to refer to Table 2, by comparing light-emitting device embodiments 1 and 5 to 7, it can be seen that compared with light-emitting device embodiment 1, since the graphene oxide nanosheet dispersion in light-emitting device embodiments 5 to 7 is alkaline, the functional layer prepared by step 3 has a basic functional group, which can neutralize the acidic molecules of the hole injection layer made of the acidic material (PEDOT / PSS) to prevent the acidic molecules from destroying the functional layer, thereby improving the LT95@1000nit and EQE of the light-emitting device; and in light-emitting device embodiments 5 to 7, as the pH value in the preparation of the alkaline graphene oxide nanosheet dispersion gradually increases, the alkalinity of the prepared functional layer with the basic functional group is stronger, which is more conducive to neutralizing the acidic molecules of the hole injection layer made of the acidic material (PEDOT / PSS), thereby further improving the LT95@1000nit and 1EQE of the light-emitting device.

[0202] (4) Continuing to refer to Table 2, by comparing light-emitting device embodiments 1 and 8 to 10, it can be seen that compared with light-emitting device embodiment 1, since light-emitting device embodiments 8 to 10 use plasma gas to treat the interface modification layer, the interface modification layer has more oxygen vacancies, which can further improve the ability to capture electron carriers, further inhibit the transmission of electron carriers to the functional layer, thereby improving the stability of the functional layer, and further improving the LT95@1000nit and EQE of the light-emitting device; and in light-emitting device embodiments 8 to 10, as the power, RF frequency, pressure and other parameters gradually increase during the plasma gas treatment, the interface modification layer after the plasma gas treatment has more oxygen vacancies, and the ability to capture electron carriers is gradually enhanced, further improving the LT95@1000nit and EQE of the light-emitting device.

[0203] (5) Continuing to refer to Table 2, by comparing light-emitting device embodiments 1, 5 and 9, it can be seen that, compared with light-emitting device embodiments 1 and 5, in the hole functional layer of light-emitting device embodiment 9, not only does the functional layer have a basic functional group that can neutralize the acidic molecules of the hole injection layer made of the acidic material (PEDOT / PSS), but also the interface modification layer is treated with plasma gas, which increases the number of oxygen vacancies in the interface modification layer, further improving the LT95@1000nit and EQE of the light-emitting device.

[0204] Obviously, the embodiments described above are only some embodiments of the present application, rather than all embodiments. The preferred embodiments of the present application are given in the accompanying drawings, but they do not limit the patent scope of the present application. The present application can be implemented in many different forms. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive. Although the present application is described in detail with reference to the aforementioned embodiments, for those skilled in the art, it is still possible to modify the technical solutions recorded in the aforementioned specific implementation methods, or to perform equivalent replacement of some of the technical features therein. Any equivalent structure made using the contents of the specification and drawings of this application, directly or indirectly used in other related technical fields, is similarly within the scope of patent protection of this application.

Claims

1. A composite film, characterized in that: It includes a functional layer and an interface modification layer stacked in sequence; The material of the functional layer includes a first metal oxide; the material of the interface modification layer includes a second metal oxide and a metal chalcogenide.

2. The composite film according to claim 1, characterized in that The first metal oxide and the second metal oxide independently include at least one of cuprous oxide, ferric oxide, manganese oxide, tungsten dioxide, and nickel oxide; and / or, The metal element of at least two of the first metal oxide, the second metal oxide and the metal chalcogenide compound is the same; and / or, The mass ratio of the second metal oxide to the metal chalcogenide compound in the interface modification layer is 1:(0.2-0.5); and / or, The weight percentage of oxygen in the second metal oxide is 10-50wt%; and / or, The thickness ratio of the functional layer to the interface modification layer is (30-50):(5-10).

3. The composite film according to claim 1, characterized in that The functional layer further comprises a carbon material, and the first metal oxide is supported on the carbon material; and / or, The carbon material includes at least one of graphene oxide, carbon fiber, carbon nanotube, carbon 60, graphite, and activated carbon; and / or, The surface of the carbon material is modified with basic functional groups, wherein the basic functional groups include hydroxyl functional groups and / or amino functional groups; and / or, The mass ratio of the carbon material to the first metal oxide is 1:(0.5-1.2); and / or, The weight percentage of carbon element and metal element in the functional layer is (3-8):

1.

4. The composite film according to any one of claims 1 to 3, characterized in that The material of the interface modification layer includes a core body and a shell layer covering the core body, the core body includes the second metal oxide, and the shell layer includes the metal chalcogenide compound.

5. The composite film according to claim 4, characterized in that The particle size of the material of the interface modification layer is 2 to 8 nm; and / or, The ratio of the thickness of the shell layer to the diameter of the core body is 1:(2-8); and / or, The metal chalcogenide compound includes at least one of metal sulfide, metal selenide and metal telluride; and / or, The metal sulfide includes at least one of cuprous sulfide, iron sulfide, manganese sulfide, tungsten disulfide and nickel sulfide; and / or, The metal selenide includes at least one of cuprous selenide, iron selenide, manganese selenide, tungsten diselenide and nickel selenide; and / or, The metal telluride includes at least one of cuprous telluride, iron telluride, manganese telluride, tungsten ditelluride, and nickel telluride; and / or, The metal elements of the first metal oxide, the second metal oxide and the metal chalcogenide are all the same.

6. A method for preparing a composite film, characterized in that: include: providing a substrate; Disposing a functional material solution on the substrate to form a functional layer, wherein the functional material solution includes a first metal oxide; An interface modification solution is arranged on the functional layer to form an interface modification layer to obtain a composite film, wherein the interface modification solution includes a second metal oxide and a metal sulfide compound.

7. The method for preparing a composite film according to claim 6, characterized in that: Before the step of obtaining the composite film, the method further comprises: Plasma gas is provided to the interface modification layer for etching.

8. The method for preparing a composite film according to claim 7, characterized in that: The plasma gas includes at least one of argon, hydrogen and nitrogen; and / or, The etching treatment time is 10 to 60 minutes; and / or, The power of the etching process is 110 to 160 W; and / or, The radio frequency of the etching process is 10 to 15 MHz; and / or, The pressure of the etching process is 80-120Pa.

9. The method for preparing a composite film according to any one of claims 6 to 8, characterized in that: The functional material solution further includes a carbon material, and the first metal oxide is supported on the carbon material; and / or Before the step of providing the functional material solution on the substrate, the method further comprises: Providing a first metal oxide precursor solution and a carbon material solution; mixing the first metal oxide precursor solution and the carbon material solution to obtain a first mixed solution; Drying the first mixed solution to obtain a functional material; mixing the functional material and a first organic solvent to obtain a functional material solution; and / or The first metal oxide includes at least one of cuprous oxide, ferric oxide, manganese oxide, tungsten dioxide, and nickel oxide.

10. The method for preparing a composite film according to claim 9, characterized in that: The volume ratio of the first metal oxide precursor solution to the carbon material solution is (0.01-0.5):1; and / or, The first metal oxide precursor solution comprises a first metal oxide precursor and a first solvent; and / or, The carbon material solution comprises a carbon material and a second solvent; and / or, The first organic solvent includes at least one of aromatic hydrocarbon solvents, aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, halogenated hydrocarbon solvents, alcohol solvents, ether solvents, ester solvents, ketone solvents, glycol derivative solvents, acetonitrile, and pyridine; the aromatic hydrocarbon solvent includes at least one of benzene, toluene, and xylene; the aliphatic hydrocarbon solvent includes at least one of pentane, hexane, and octane; the alicyclic hydrocarbon solvent includes at least one of cyclohexane, cyclohexanone, toluene, and cyclohexanone; the halogenated hydrocarbon solvent includes at least one of chlorobenzene, dichlorobenzene, and dichloromethane; the alcohol solvent includes at least one of methanol, ethanol, and isopropanol; the ether solvent includes at least one of ethyl ether and propylene oxide; the ester solvent includes at least one of methyl acetate, ethyl acetate, and propyl acetate; the ketone solvent includes at least one of acetone, methyl butyl ketone, and methyl isobutyl ketone; the glycol derivative solvent includes at least one of ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, and ethylene glycol monobutyl ether.

11. The method for preparing a composite film according to claim 10, characterized in that: The concentration of the first metal oxide precursor in the first metal oxide precursor solution is 0.01 to 0.05 g / mL; and / or, The concentration of the carbon material in the carbon material solution is 0.02 to 0.05 g / mL; and / or, The first metal oxide precursor includes at least one of copper acetate, ferric phosphate, manganous oxalate, ammonium tungstate, and nickel nitrate; and / or, The first solvent includes an aromatic hydrocarbon solvent, and the aromatic hydrocarbon solvent includes at least one of benzene, toluene and xylene; and / or, The carbon material includes at least one of graphene oxide, carbon fiber, carbon nanotube, carbon 60, graphite, and activated carbon; and / or, The second solvent includes an alcohol solvent, N,N-dimethylformamide, and deionized water, and the alcohol solvent includes at least one of methanol, ethanol, and isopropanol.

12. The method for preparing a composite film according to any one of claims 6 to 8, characterized in that: Before the step of providing the interface modification solution on the functional layer, the method further comprises: providing a second metal oxide precursor solution and a metal chalcogenide precursor solution; mixing the second metal compound precursor solution and the metal chalcogenide compound precursor solution to obtain a second mixed solution; mixing the second mixed solution and a second organic solvent to obtain an interface modification solution; and / or The second metal oxide includes at least one of cuprous oxide, ferric oxide, manganese oxide, tungsten dioxide, and nickel oxide; and / or The metal chalcogenide compound includes at least one of a metal sulfide, a metal selenide, and a metal telluride; and / or The metal element of at least two of the first metal oxide, the second metal oxide and the metal chalcogenide is the same; and / or The interface modification solution includes an interface modification layer material, the interface modification material includes a core body and a shell layer covering the core body, the core body includes the second metal oxide, and the shell layer includes the metal sulfide compound.

13. The method for preparing a composite film according to claim 12, characterized in that: The volume ratio of the second metal oxide precursor solution to the metal chalcogenide compound precursor solution is 1:(5-10); and / or, The second metal oxide precursor solution includes a second metal precursor and a third solvent; and / or, The metal chalcogenide compound precursor solution comprises a metal chalcogenide compound precursor and a fourth solvent; and / or, The second organic solvent includes at least one of aromatic hydrocarbon solvents, aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, halogenated hydrocarbon solvents, alcohol solvents, ether solvents, ester solvents, ketone solvents, glycol derivative solvents, acetonitrile, and pyridine; the aromatic hydrocarbon solvent includes at least one of benzene, toluene, and xylene; the aliphatic hydrocarbon solvent includes at least one of pentane, hexane, and octane; the alicyclic hydrocarbon solvent includes at least one of cyclohexane, cyclohexanone, toluene, and cyclohexanone; the halogenated hydrocarbon solvent includes at least one of chlorobenzene, dichlorobenzene, and dichloromethane; the alcohol solvent includes at least one of methanol, ethanol, and isopropanol; the ether solvent includes at least one of ethyl ether and propylene oxide; the ester solvent includes at least one of methyl acetate, ethyl acetate, and propyl acetate; the ketone solvent includes at least one of acetone, methyl butyl ketone, and methyl isobutyl ketone; the glycol derivative solvent includes at least one of ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, and ethylene glycol monobutyl ether.

14. The method for preparing a composite film according to claim 13, characterized in that: The concentration of the second metal precursor in the second metal oxide precursor solution is 0.2 to 0.8 mol / L; and / or, The second metal precursor includes at least one of copper acetate, ferric phosphate, manganous oxalate, ammonium tungstate, and nickel nitrate; and / or, The third solvent includes an aromatic hydrocarbon solvent, and the aromatic hydrocarbon solvent includes at least one of benzene, toluene and xylene; and / or, The fourth solvent includes at least one of aromatic hydrocarbon solvents, alcohol solvents, ether solvents, ester solvents, and ketone solvents; the aromatic hydrocarbon solvent includes at least one of benzene, toluene, and xylene; the alcohol solvent includes at least one of methanol, ethanol, and isopropanol; the ether solvent includes at least one of ether and propylene oxide; the ester solvent includes at least one of methyl acetate, ethyl acetate, and propyl acetate; the ketone solvent includes at least one of acetone, methyl butyl ketone, and methyl isobutyl ketone; and / or, The concentration of the metal chalcogen compound precursor in the metal chalcogen compound precursor solution is 1 to 5 mol / L; and / or, The metal chalcogenide compound precursor includes at least one of a metal sulfide precursor, a metal selenide precursor, and a metal telluride precursor; and / or, The metal sulfide precursor is selected from at least one of sodium sulfide, potassium sulfide, calcium sulfide, magnesium sulfide, aluminum sulfide and zinc sulfide; and / or, The metal selenide precursor is selected from at least one of sodium selenide, potassium selenide, calcium selenide, magnesium selenide, aluminum selenide, and zinc selenide; and / or, The metal telluride precursor is selected from at least one of sodium telluride, potassium telluride, calcium telluride, magnesium telluride, aluminum telluride, and zinc telluride.

15. A light emitting device, characterized in that: It includes a first electrode, a hole functional layer, a light-emitting layer and a second electrode stacked in sequence; Wherein, the hole functional layer comprises a composite film, and the composite film is a composite film as claimed in any one of claims 1 to 5, or is made by the composite film preparation method as claimed in any one of claims 6 to 14.

16. The light emitting device according to claim 15, characterized in that: The functional layer is disposed close to the first electrode, and the interface modification layer is disposed close to the light-emitting layer; and / or, The materials of the first electrode and the second electrode independently include at least one of a metal material, a carbon material and a metal oxide, the metal material includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes a doped or undoped metal oxide, the doped metal oxide includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, or includes a composite electrode in which a metal is sandwiched between doped or undoped transparent metal oxides, the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or, The light-emitting layer is a quantum dot light-emitting layer or an organic light-emitting layer; the material of the quantum dot light-emitting layer includes at least one of a single structure quantum dot and a core-shell structure quantum dot, and the material of the single structure quantum dot, the core material of the core-shell structure quantum dot and the shell material of the core-shell structure quantum dot are independently selected from at least one of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds, wherein the II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, C At least one of dSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, wherein the IV-VI group compound is selected from SnS, Sn At least one of SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe, and the III-V group compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNA s, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs or InAlPSb, and the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2;The material of the organic light-emitting layer includes at least one of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine-C2,N)iridium(III), 4,4',4"-tris(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine-C2,N)iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials and DBP fluorescent materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives; and / or; The light-emitting device further includes a hole injection layer disposed between the first electrode and the composite film; the material of the hole injection layer includes at least one of TFB, CuPc, PVK, Poly-TPD, PFB, DNTPD, TCATA, TCCA, CBP, TPD, NPB, NPD, PEDOT:PSS, TAPC, MCC, F4-TCNQ, HATCN, 4,4',4'-tris(N-3-methylphenyl-Nphenylamino)triphenylamine, polyaniline, transition metal oxides, transition metal sulfides, transition metal tin compounds, doped graphene, non-doped graphene, C60, polyester copper carbonate, and molybdenum trioxide; and / or, The light-emitting device further comprises an electron transport layer and / or an electron injection layer arranged between the light-emitting layer and the second electrode; the materials of the electron transport layer and the electron injection layer independently comprise inorganic materials and / or organic materials respectively; the inorganic materials comprise one or more of doped or undoped zinc oxide, barium oxide, aluminum oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, aluminum zinc oxide, manganese zinc oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate, and the doped elements comprise at least one of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic materials comprise at least one of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, hydroxyquinoline compounds, polythiophene compounds, perylene imide compounds, and fullerene compounds.

17. A display device, characterized in that: including a light emitting device; Wherein, the light-emitting device is the light-emitting device as claimed in any one of claims 15 or 16.